When Prosecution Is Declined: Factors Influencing Prosecutorial Portrayal of Officers Involved in Shootings - Herrera, Jacob (Criminal justice policy review, 2023)
Using District Attorney Declination Letters of officer-involved shootings in Denver, Colorado between 2000 and 2020 (N = 132) and drawing on the Narrative Policy Framework, this study examined how prosecutors use of narrative strategies varied with legal and extra-legal characteristics of shooting. Findings indicated that prosecutors were more likely to likely to praise police shootings involving armed subjects, independent witnesses, and injuries to officers. Surprisingly, prosecutors were less likely to praise officers involved in the shooting of African American subjects, unarmed suspects, and in shootings involving a standoff. Findings suggest that while prosecutors largely draw upon legal criteria to justify not prosecuting police, their narrative accounts of declining to pursue criminal charges are also sensitive to extra-legal variables. Implications for theory, practice, and research are discussed.